GRAMMATICAL ANALYSIS OF ACTION AND OBJECT NAMING SKILLS OF TURKISH APHASIC PATIENTS - Gülmira KURUOĞLU (Fırat University, 2019)
Language consists of various cognitive processes like speaking, comprehension, reading, writing, repeating and naming. Aphasia, an acquired language disorder, results from deficits occurred in the components of these processes. Communication problem is one of the most important problems observed in patients with aphasia and the most important element that deteriorates communication is the naming deficit of these patients. In this study it is aimed to make a linguistic analysis of naming deficits of Turkish aphasic patients. Goals of the research are to elucidate the relationship between object and action naming deficits and aphasia type Turkish speaking in